Secondary fibromyalgia in children with immune-inflammatory rheumatic diseases - A. V. Santimov; S. V. Grechanyi; G. A. Novik (Современная ревматология, 2024)
Patients with immune-inflammatory rheumatic diseases (IIRDs) often present with non-inflammatory musculoskeletal pain associated with nociceptive dysfunction, central sensitization, and secondary fibromyalgia (FM). In recent years, an increasing number of publications have appeared dealing with FM in rheumatoid arthritis and systemic connective tissue diseases in adult patients, while this problem is little discussed in pediatric rheumatology, partly due to the differences between the existing diagnostic criteria in children and adults, which complicate the diagnosis of juvenile secondary FM. The consequence of this is often the unfounded prescription or switching of synthetic disease-modifying antirheumatic drugs (DMARDs) or biologic DMARDs in patients who do not require intensified antirheumatic therapy, but rather psychotherapy and psychopharmacotherapy, as well as the wider use of physical and rehabilitation medicine methods. In a brief narrative review, we tried to trace the investigation of FM in a rheumatological clinic, including children with IIRD, from a historical perspective, to summarize current literature data on this problem and to point out possible solutions.